从损害填补迈向风险治理：法典化视域下预防性环境公益诉讼的体系构建 - 浪 洪; 瑞怡 侯; 黔 赵 (科学与技术探索, 2026)
The Eco-Environmental Code establishes the logic of comprehensive risk governance, driving the transformation of environmental rule of law from ex-post damage remediation to ex-ante source prevention and control. As the core judicial carrier for implementing the precautionary principle, preventive environmental public interest litigation enables early intervention against major ecological risks that have not caused substantive damage. At the current stage, this system faces practical dilemmas including insufficient legislative supply, inconsistent criteria for identifying major risks, imbalance in the burden of proof between two parties, absence of administrative preventive litigation, and conservative application of preventive remedies. Against the backdrop of codification reform, this paper analyzes the inherent drawbacks of traditional end-stage environmental judicature, elaborates the unique institutional value of preventive environmental public interest litigation, and sorts out operational bottlenecks of the system at the legislative and judicial levels. On this basis, the paper proposes improvement approaches from four dimensions: integrating legislative norms, establishing unified graded and classified identification rules for major risks, optimizing special litigation procedures, and improving supporting guarantees for technical professionals. It aims to build a full-chain judicial risk protection system featuring coordinated interaction among administration, judicature and society, advance the standardized and regular operation of preventive environmental public interest litigation, and consolidate the judicial defense line for ecological security.